A taxonomic study of the South African terricolous weevil genus Pentatrachyphloeus Voss (Coleoptera: Curculionidae: Entiminae: Trachyphloeini) - Borovec, Roman; Skuhrovec, Jiří (Zootaxa, 2019)
The genus Pentatrachyphloeus Voss, 1974, with two known species, is redefined and compared with related genera. An additional thirty seven new species are described here: P. andersoni sp. nov. (South Africa, Mpumalanga); P. baumi sp. nov. (South Africa, Gauteng); P. brevithorax sp. nov. (South Africa, KwaZulu-Natal); P. bufo sp. nov. (South Africa, Mpumalanga); P. endroedyi sp. nov. (South Africa, Mpumalanga); P. exiguus sp. nov. (South Africa, Mpumalanga); P. frici sp. nov. (South Africa, Limpopo); P. grobbelaarae sp. nov. (South Africa, KwaZulu-Natal); P. hanzelkai sp. nov. (South Africa, KwaZulu-Natal); P. holubi sp. nov. (South Africa, Mpumalanga); P. howdenae sp. nov. (South Africa, Mpumalanga); P. hystrix sp. nov. (South Africa, Mpumalanga); P. insignicornis sp. nov. (South Africa, KwaZulu-Natal); P. kalalovae sp. nov. (South Africa, Gauteng); P. kuscheli sp. nov. (South Africa, KwaZulu-Natal); P. laevis sp. nov. (South Africa, Mpumalanga); P. lajumensis sp. nov. (South Africa, Limpopo); P. leleupi sp. nov. (Zimbabwe, Manica); P. lesothoensis sp. nov. (Lesotho, Qacha’s Nek); P. machulkai sp. nov. (South Africa, Free State); P. marshalli sp. nov. (South Africa, KwaZulu-Natal); P. muellerae sp. nov. (South Africa, Mpumalanga); P. musili sp. nov. (South Africa, Limpopo); P. ntinini sp. nov. (South Africa, KwaZulu-Natal); P. oberprieleri sp. nov. (South Africa, Gauteng, North West); P. pavlicai sp. nov. (South Africa, Free State); P. rudyardi sp. nov. (South Africa, Limpopo); P. schoemani sp. nov. (South Africa, Limpopo); P. soutpansbergensis sp. nov. (South Africa, Limpopo); P. spinimanus sp. nov. (South Africa, Mpumalanga); P. stingli sp. nov. (South Africa, Limpopo); P. tenuicollis sp. nov. (South Africa, Mpumalanga); P. tuberculatus sp. nov. (South Africa, Mpumalanga); P. vavrai sp. nov. (South Africa, Eastern Cape); P. vossi sp. nov. (South Africa, Mpumalanga); P. vrazi sp. nov. (South Africa, Limpopo) and P. zikmundi sp. nov. (South Africa, Free State). All of the species are keyed and illustrated; ecological information is presented only where available. All species seem to be very localised, being known only from one or only a very limited number of localities. Immature stages or host plants are not known for any of the species. The species are distributed as follows: South Africa: Mpumalanga (13), Limpopo (8), KwaZulu-Natal (7), Free State (3), Gauteng (3), Eastern Cape (3), North West (1); Lesotho: Qacha’s Nek (1) and Zimbabwe: Manica (1).